The Role of Virtual Laboratories in Inquiry-Based Learning Models for Improving Understanding of Physics Concepts: A Literature Review - Aulia, Aulia; Adawiah, Robiatul; Lutfiatussolihah, Lutfiatussolihah (Indonesian Publication Center, 2024)
Physics education often faces the challenge of limited access to real-world laboratory facilities, which results in low levels of students’ conceptual understanding. This study aims to analyze the role of virtual laboratories in the Inquiry-Based Learning (IBL) model to enhance students’ understanding of physics concepts through a systematic literature review of 15 scientific articles (2015–2024) from the Google Scholar, ProQuest, and ERIC databases. The research method employed thematic analysis and tabular synthesis to compare the subjects, methods, and results of the studies. The findings indicate that the integration of virtual laboratories into the IBL model consistently improves students’ conceptual understanding, with learning achievement rates reaching 80–85% and N-gain values in the moderate to high range (0.38–0.73). This model is most effective when applied to abstract material due to its ability to visualize dynamic physical phenomena. However, the effectiveness of this model is highly dependent on the quality of teachers’ instructional design and the availability of technological devices in schools.